2017
DOI: 10.5005/jp-journals-10032-1118
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in Black South African Women: Myth or Reality

Abstract: Aim The study was conducted to ascertain the severity of the occurrence of osteopenia and osteoporosis among black South African women during their transition from premenopause to postmenopause. Materials and methods Sixty-eight black South African women, aged between 32 and 77 years, residents of three districts of Pretoria, South Africa, constituted the participants in the study. Following informed consent, the women were randomly recruited and assessed for age, medical history, and lifestyle data. Each wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…We have shown that, as in other populations globally, ( 41 ) black South African women transitioning through menopause experience substantial declines in BMD across all skeletal sites, and those transitioning into or who are in postmenopause exhibit the greatest losses. Our data add to the findings of a small cross‐sectional study of 68 black South African women that showed that postmenopausal women had lower LS and hip BMD than pre‐ or perimenopausal women ( 42 ) and earlier results from 709 black South African women in Soweto, from which this follow‐up cohort was derived, which found lower TB BMD in postmenopausal than pre‐ or perimenopausal women. ( 43 ) Our data are novel in their longitudinal nature in SSA.…”
Section: Discussionsupporting
confidence: 77%
“…We have shown that, as in other populations globally, ( 41 ) black South African women transitioning through menopause experience substantial declines in BMD across all skeletal sites, and those transitioning into or who are in postmenopause exhibit the greatest losses. Our data add to the findings of a small cross‐sectional study of 68 black South African women that showed that postmenopausal women had lower LS and hip BMD than pre‐ or perimenopausal women ( 42 ) and earlier results from 709 black South African women in Soweto, from which this follow‐up cohort was derived, which found lower TB BMD in postmenopausal than pre‐ or perimenopausal women. ( 43 ) Our data are novel in their longitudinal nature in SSA.…”
Section: Discussionsupporting
confidence: 77%